ANALISIS KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN LINEAR SATU VARIABEL DITINJAU DARI GAYA BELAJAR - Putra, Yudi Anggara; Susanto, S; Suharto, S (Kadikma, 2019)
This study focused on analyzing students’ communication skill in solving linear equitation of one variable viewed from learning styles. The subjects were students of class VII D in SMPN 1 Jember. The tests consisted of learning styles questionnaire to group their learning style, written communication skill test, and interview. The subject of this research is one of each learning styles. The result showed that students with impulsive kinesthetic learning style are not able to fulfill all written mathematical communication indicators, but they are able to fill 1 of 6 written communication skill indicators, then audio students are able to fulfill 3 of 5 written mathematical communication indicators and fill 5 of 6 interviev indicators, whereas visual students are able to fulfill 4 of 5 written mathematical communication indicators and fill all of interview indicators. Keywords: Communication skill, learning style, visual, audio, kinesthetic